C60-Decorated nickel–cobalt phosphide as an efficient and robust electrocatalyst for hydrogen evolution reaction. Issue 48 (4th December 2018) - Du, Zhiling; Jannatun, Nahar; Yu, Danyang; Ren, Juan; Huang, Wenhuan; Lu, Xing
Abstract : High-activity electrocatalysts play a crucial role in energy conversion through splitting water to produce hydrogen. Abstract : High-activity electrocatalysts play a crucial role in energy conversion through splitting water to produce hydrogen. Here we report the synthesis of a bimetallic phosphide of Ni–Co–P coupled with C60 molecules which acts as an electrocatalyst for the hydrogen evolution reaction (HER). Powder X-ray diffraction (XRD) and transmission electron microscopy (TEM) characterization reveals that the synthesized C60 -decorated Ni–Co–P nanoparticles have an average diameter of ∼4 nm with rich structural defects. Electrochemical tests show that the as-synthesized C60 -decorated Ni–Co–P catalyst with a C60 -content of 3.93 wt% presents a low onset overpotential of 23.8 mV, a small Tafel slope value of 48 mV dec −1, and excellent hydrogen-evolution stability with a slight increase of its η 10 from 97 mV to 102 mV after 500 cycles. Additionally, electrochemical impedance spectroscopy (EIS) confirms that the C60 -decorated Ni–Co–P electrode possesses faster charge-transfer kinetics and hydrogen-adsorption kinetics than the C60 -free Ni–Co–P electrode during the HER process. The synthesis of a C60 -decorated composite is feasible and the composite can be used as an efficient and robust Pt-free catalyst.